You are on page 1of 7

# :

2006
n http://arabmaths.ift.frn

:
cherifalix@yahoo.fr

:
u 0 = 4

1
9
u n +1 = 4 u n + 4

) : (u n

) (vn :

u n = vn + 3

lim u n = 3

n +

______________________________________

vn = u n + k

) k ( n

) (E ) (O; i ; j ; k

(1 vn+1 u n . vn

## A(2;0;2 ) : ) B(1;1;3 )C (0;2;1

9
1
v n +1 = u n +1 + k = .u n + + k
4
4
1
9
= (v n k ) + + k
4
4

(1

AB( 1 ; 1 ; 1) : )AC ( 2 ; 2 ; 1

1 1
1 1
1 1
.i
.j +
.k :
2 1
2 1
2 2

1
3
9
v n +1 = .v n + .k +
4
4
4

(2 k ) (vn .
:

3
9
.k + = 0
4
4

AB AC

1
) (vn
4

(3 ) (u n ) . (vn

n 0

v0 = 1
1
= vn
4

1
:
v n = v0 .
:
4
1
lim v n = 0
0 1 : :
n +
4

vn = u n + k

ABC

( ABC ) : 3x 3 y + d = 0

( ABC ) : 3x 3 y 6 = 0

(3 ) (S A ) ( ABC

A ( ABC ) : . d = 6 :

v0 = u 0 3 = 1

1
) (vn
4

= AB AC

AB AC = 3i 3 j

(2 ) ( ABC

k = 3

: AB AC

u n = vn k

) ( B . 2
R ) (S r ) . (

:
= 3 :

d 2 + r 2 = R2

( 1)2 + ( 1)2 + 12

= d = AB

. r=2

R = d 2 r2 = 3+ 4 = 7

:

:
:

2006
o http://arabmaths.ift.fro

:
cherifalix@yahoo.fr

( x 2 )2 + y 2 + ( z 2 ) 2 = 7

: X

x 2 + y 2 + z 2 4x 4z + 1 = 0

_________________________________
:

10

1
10

1
2

2
5

) = xi

(X

) P( X = xi

, ,
.

- ) : E ( X

- 1 :

i =1

" : J "
" : B "
" : R "
" : V "

) E ( X ) = xi .P( X = xi

3
10
2 1
= ) P (B
=
10 5
1
= ) P (R
10
4 2
= ) P(V
=
10 5

= ) P( J

- 2
:
10 . . 3 .
X
.
- . X
:

1 33
1
2
= = 2. + 3. + 10.
10 10
2
5

}X ( ) = {2;3;10

2
:
5
) P ( X = 3) = P ( J B ) = P ( J ) + P ( B ) P ( J B
3 1 1
=
= +
10 5 2
1
= ) P( X = 10) = P(R
10
= ) P( X = 2) = P(V

) : V ( X2

)) V ( X ) = pi .( xi E ( x
i =1

2
33
1
33
1
33
= . 2 + . 3 + .10
5
10
2 10 10
10

______________________________________

8 z + 24 z 32 = 0 :
2

z0 = 4 ( 1

) (E

(E ) : z

4 8 4 + 24 4 32 = 0
3

a b c ) (E :
+ bz + c ) = 0

(E ) : (z 4)(az

2

(z 4)(a.z

4.a.z 2 4.b.z 4c

) (E * :

## a.z 3 + (b 4a ).z 2 + (c 4b ).z 4c

= z 3 8.z 2 + 24.z 32

2006
p http://arabmaths.ift.frp

:
cherifalix@yahoo.fr

a = 1
b 4a = 8

c 4b = 24
4c = 32

:
f x :

f (x ) = xx ++ 12 + ln x + 1

a = 1
b = 8 + 4 = 4

c = 24 + 4b = 24 16 = 8

c = 32 = 8

4
a = 1

b = 4
c = 8

(1 - : f

- x : D f

(E ) : (z 4)(z 2 4.z + 8) = 0

- 2 ) . (E z1 z 2

) (E (E ) : (z 4)(z 2 4.z + 8) = 0 :
(z 2 4.z + 8) = 0 : (z 4) = 0
2
' = 4 8 = 4 = (2i ) : (z 2 4.z + 8) = 0
z1 = 2 + 2.i :

} :

z1

z1 = 2 2 .e 4 : z 2

z 2 z = 2i = 2

M 0 = M 1 = M 2 :
M 2 ; M 1 ; M 0

= 2 . R = 2

x 1+

t 0 +

t 0

lim f (x ) = +

3 M 2 ; M 1 ; M 0

z 0 z = 4 2 = 2 : z1 z = 2i = 2

) lim x + 2 + (xx++11)ln(x + 1) ( x + 1 0
lim t.ln(t ) = 0 : t = x + 1 :

z 2 = 2 2 .e

z 2 ; z1 ; z0 ) (
= 2 R = 2

x +1

x 1+

- - ) f (

S = { 4 ; 2 + 2i ; 2 2i

x 1+

z 2 = 2 2.i

f (x ) = x + 2 + (xx++11)ln x + 1
lim f (x ) = lim x + 2 + (x + 1)ln x + 1

t 0 + x 1+
:
) t + 1 + t ln(t
(
)
f
x
=
= + :
lim
lim
+
x 1+

Im( z1 ) 0 . Im( z 2 ) 0

}D f = IR { 1

:
.

x +

lim f (x ) = +
x

lim f (x ) =
x 1

x
(x + 1)2

= ) f '(x

) (x D f

2006
q http://arabmaths.ift.frq

:
cherifalix@yahoo.fr

1 x
2

)( x + 1

= ) (x D ) : f ' ' ( x
f

(C ) : )) I (1 ; f (1 .
:

x + 1 ln x + 1
.
x
x +1

x+2

x x +1

= lim
x

)(

f x

lim
x

=0
) (C

) (C

: :
( 1
.
( 2 .
( 3

: - 2

) y = ( x + 2)f ' ( 2 ) + f ( 2

) (C

( 6 :

:
*

x 1+

lim f ( x ) =
x 1

) (C

x = 1 :
. - 1

5
1
)y = x + + ln(2
4
4
lim f ( x ) = + :

( 4 .

( 5 ) (C

y = 2 x 4
- )): I (1 ; f (1

## )y = (x 1)f ' (1) + f (1

) . (

:

:

2006
r http://arabmaths.ift.frr

:
cherifalix@yahoo.fr

) (C

) f (x

x1

.
(3

## x+1 .ln x+1

x1

)= 0 = g(1

:
-

: 1

* :

)x + 1)e( x +1). ln ( x +1
)g( x ) g(1
(
= xlim
=1
lim
x 1
1
x +1
x +1
+

)g(x) g( 1
) (x + 1)e( ( x+1)).ln( x+1
= lim
= 1
x1
x +1
x +1

; x 1

(
g ( x ) = e

g ( 1) = 0

x + 2 ) ln x +1

x 1

( 1 -
x +1 ) ln x +1

( g(x ) = x + 1 e

x + 1 ln x + 1 + ln x + 1

x + 1 ln x + 1

## (x IR {1}) : g'(x) = f (x).e( ) :

) g ( x ) . f ( x
x+2 .ln x+1

: g

g( x ) = e

ln x + 1

e
e

(3 - :

=
=

x 1

g ( x ) = x + 1 e ( x +1)ln x+1

) = x +1

ln x +1

(e

x + 1 ( x +1). ln x +1
) g (x
.e
= lim
x +
x
x
(x + 1) .e ( x +1). ln ( x +1) = +
= lim
x +
x

: 1

) x +1 ) . ln ( x +1

* :

(2

}. IR { 1

x1

( g(x ) = e

x + 1 + 1 ln x + 1

. 1

lim

x 1
x + 2 ) ln x +1

## ( lim g ( x ) = lim(x + 1).e

+

x 1

)= 0 = g ( 1

x 1

lim
x +

:

g

( 4 :

2006
s http://arabmaths.ift.frs

:
cherifalix@yahoo.fr

= x +1

1
x+2

: m

x IR

:
:

x+2

x+2

= x +1

m x+2

m = e ( x + 2 ).ln x+1
g (x ) = m

) (
y = m

x IR

_1

m 0

: .

_ 2

m=0

. - 1
_3

0 m 1

.
_ 4 :

m =1

: 2

.0 _ 5 :

m 1

: .